Etika warga negara saat berinteraksi dalam ruang publik digital perspektif pancasila - Kamal, Muhammad Zulfa; Muzakky, Muhammad Khayyi; Wijaya, Eka Teguh (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the importance of ethics in expressing opinions and ideas in public spaces. This research is categorized as qualitative research using literature studies. The data obtained in this study is then processed to become a conclusion. Pancasila has basic values in the five precepts in it. Democracy is part of the realization of the basic values of Pancasila. This democracy is called Pancasila Democracy. In Pancasila Democracy, the rights of citizens in opinion are still guaranteed by the state. On the other hand, Pancasila also acts as a national philosophy to invite someone who expresses to always prioritize ethics in voicing opinions or ideas. By practicing ethics in opinion, especially in public spaces, social order can be achieved.